IMPROVING STUDENTS’ PRONUNCIATION IN SPEAKING BY USING PODCAST AS MEDIA - Mellisa Mellisa; Rahayu Apriliaswati; Eusabinus Bunau (Universitas Tanjungpura, 2021)
AbstractThis study aimed to improve students’ pronunciation in Speaking by using Podcast as media to the tenth class of MIA (matematika Ilmu Alam) 1 of SMA Negeri 01 Sandai in the academic year 2019/2020. In this research, the researcher applied Podcast as media to solve students’ problems. The method of this research is classroom action research. This research was conducted in two cycles. The data was collected through observation checklist, field note, and speaking assessment. The subject of the research was thirty-five students of the tenth class of MIA (Matematika Ilmu Alam) 1. The findings showed that during the teaching and learning process, the students’ pronunciation improves through drilling and roleplay activities. The students were active following the activity in the classroom. The implementation of podcast as media teaching had caused students to engage with the lesson and behavioral changes in students learning which led the improvement on the students' pronunciation. It is seen from the result of the speaking assessment on cycle 2. Based on the improvement, it is concluded that podcast improves students’ pronunciation on consonant /f/ and /v/.Keywords: Classroom Action Research, Podcast, Pronunciation.